1989
DOI: 10.1093/nar/17.2.553
|View full text |Cite
|
Sign up to set email alerts
|

Replication timing of 10 developmentally regulated genes inPhysarum polycephalum

Abstract: We have tested the hypothesis which stipulates that only early-replicating genes are capable of expression. Within one cell type of Physarum - the plasmodium - we defined the temporal order of replication of 10 genes which were known to be variably expressed in 4 different developmental stages of the Physarum life cycle. Southern analysis of density-labeled, bromodesoxyuridine-substituted DNA reveals that 4 genes presumably inactive within the plasmodium, were not restricted to any temporal compartment of S-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 38 publications
2
24
1
Order By: Relevance
“…However, we also found that the highly expressed php gene is late replicated in plasmodia (21,22). Here, we used neutral bidimensional agarose gel electrophoresis (2D-gel) method (23) to determine whether php gene late replication comes from its association to a late firing origin or from its long distance from an early firing origin.…”
Section: Introductionmentioning
confidence: 56%
“…However, we also found that the highly expressed php gene is late replicated in plasmodia (21,22). Here, we used neutral bidimensional agarose gel electrophoresis (2D-gel) method (23) to determine whether php gene late replication comes from its association to a late firing origin or from its long distance from an early firing origin.…”
Section: Introductionmentioning
confidence: 56%
“…Under our stringent hybridization conditions, these two cDNAs do not cross-hybridize (Pallotta et al, 1986a;Pierron et al, 1989). Therefore, we could use the LAV3-1 and LAV 1-5 cDNAs to detect specifically the profilin A and profilin P mRNAs.…”
Section: Northern Hybridizationsmentioning
confidence: 88%
“…Given that incorporation of different amounts of exogenous histones led to distinct distributions of the tagged histones in the incorporated and free nuclear histone pools, we first monitored histones associated with specific DNA sequences by ChIP, using the ‘low’ amount of exogenous histone, as in these conditions the exogenous histones were almost entirely assembled into chromatin at the beginning of G 2 -phase (Figure 2A). To carry out these analyses, loci were chosen for their different representative chromatin structures and transcription regulation during the cell cycle (22,35,36) (Supplementary Figure S2A and B). The amount of tagged protein associated with the 5′-region, coding region and 3′-region of each locus at three time points during G 2 -phase was determined by ChIP and qPCR analyses (Figure 2B and Supplementary Figure S3A).…”
Section: Resultsmentioning
confidence: 99%